Implementsi Komunikasi Persuasif Qurani dalam Dakwah - Jufri Hasani Z (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The implementation of persuasive communication of the Qur'an in preaching is carried out by: 1. Use of polite language, 2. use of beautiful and attractive language, 3. Use of language that is straightforward, easy to understand or digest by the public, 4. Use of language that is concise and contains. 5. The language or choice of words used is able to accommodate every group. 6. Avoid using words or sentences that contain hate speech. In addition to the use of language, the way of presenting the message of da’wah also greatly determines the success of the da'wah. Every preacher is required to build good and intense relationships with the audience, including by maintaining an attitude not to monopolize the truth. The success rate of da'wah can be measured, among others, by the change in the attitude of the audience towards a better direction in accordance with the message of the message conveyed. In this study, the authors combined the concept of persuasive communication with preaching so that it gave to a persuasive da'wah model that could be applied in society. This research uses the thematic interpretation method by following the steps of contemporary interpretation where one of the points of difference with the previous method is that in the contemporary thematic interpretation method each commentator tries to answer the problems that arise by digging these answers into the Al-Qur'an